Experimental study on the fatigue behaviour of cracked steel beams repaired with CFRP plates. (August 2015) - Colombi, Pierluigi; Fava, Giulia
Highlights: Fatigue performance of cracked steel beams under constant amplitude cycling loads was explored. Fatigue repair of cracked steel beams with CFRP plates bonded to the tension flange was studied. Fatigue tests were performed under four points bending loading configuration. Analytical and numerical models were developed to predict the fatigue crack growth curves. Abstract: For the repair of damaged steel beams, Carbon Fibre Reinforced Polymers (CFRP) are effective under monotonic loads, but less information is available under fatigue loading. In this paper, fatigue tests were performed on nine CFRP reinforced cracked steel beams. The fatigue crack propagation curves showed that CFRP strips reduce the fatigue crack growth and extend the fatigue life. Experimental results also revealed the presence of a debonded area between the reinforcement and the steel substrate at the crack location. Debonding clearly has a detrimental effect on the reinforcement effectiveness. Finally, numerical and analytical studies are performed and compared to the experimental findings.